Facies heterogeneity of a Kimmeridgian Carbonate Ramp (Jabaloyas, eastern Spain): a combined outcrop and 3D geomodelling analysis. - San Miguel, G.; Aurell, M.; Bádenas, B.; Martínez, V.; Caline, B.; Pabian-Goyheneche, C.; Rolando, J.P.; Grasseau, N. (Journal of Iberian Geology, 2013)
The Upper Kimmeridgian outcrops exposed around the village of Jabaloyas (NE Spain) have been analyzed to document the facies heterogeneity across the shallow portion of a low angle carbonate ramp. The studied area covers a total surface of 12 square kilometres. Seventeen stratigraphic profiles have provided basic information to carry out the detailed facies analyses presented in this work. The studied unit corresponds to a high-frequency sequence, bounded by discontinuities that can be traced at regional scale. This sequence shows the widespread development of coral-microbial reef buildups with conical to cylindrical shape (up to 19 m thick). The characterization and interpretation of the different sort of inter-reef and post-reef facies resulted in the reconstruction of the sedimentary domains of the studied carbonate ramp, from burrowed mud-dominated skeletal facies (distal middle ramp), to grainy (skeletal, peloidal, oolitic) shoal and backshoal facies (inner ramp). The studied sequence is divided into four sedimentary episodes bounded by sharp facies changes. The lower two episodes include the vertical reef growth during rapid accommodation gain; the upper two episodes are marked by the rapid progradation of the inner ramp facies. The depositional facies and their stacking patterns in the Jabaloyas outcrops are similar to those described in the subsurface Arab D reservoirs. This Late Jurassic carbonate unit forms major hydrocarbon fields in the Middle East. For improving the geological distribution of reservoir heterogeneity in this kind of low angle carbonate ramp system, two 3D models have been created. A Fullfield Model of the overall geometry of the facies belts has allowed the quantification of vertical and lateral extension of the inter-reef and post-reef facies. A Sector Model, which includes individual reef bodies has been used to better simulate reservoir heterogeneity resulting from different diagenetic overprint.